Religious Traditions in Balun-Turi Village, Lamongan: Representation of Religious and Cultural Harmony in Indonesia - Rofi’i, Muhammad Arwani; Alfiani, Nurin (Proceedings of International Conference on Muslim Society and Thought, 2024)
This study aims to understand how the diversity of local religions and cultures in Balun-Turi Village, Lamongan, is reflected in religious traditions. Balun-Turi Village was chosen as a case study because it is a good representation of the religious and cultural diversity in Indonesia. The research methods used included data collection through direct observation, interviews, and analysis of related documents. The results of the study revealed that Balun-Turi Village has various rich and diverse religious traditions. These traditions include religious celebrations, rituals, and other religious practices carried out by various religious communities in the village. In these religious traditions, it is clear how the diversity of local religions and cultures is reflected. Data analysis showed that the religious traditions in Balun-Turi Village reflect harmony and tolerance among religions, which are characteristic of Indonesian society. Despite differences in beliefs and religious practices, the people of Balun-Turi Village live together peacefully and respect each other. This illustrates the cultural richness and religious tolerance that are integral parts of Indonesian society. These findings are important for localizing the study of religion in the Indonesian context, as they strengthen the understanding of the importance of religious and cultural diversity in building an inclusive and harmonious society. Additionally, this study emphasizes the importance of understanding and preserving local religious traditions in a broader context as part of efforts to preserve the cultural heritage of the nation. In conclusion, this study makes an important contribution to supporting local religious and cultural diversity and localizing the study of religion in the Indonesian context